Human Immunodeficiency Virus Infection Increases the Risk of Incident Autoimmune Hemolytic Anemia: A Population-Based Cohort Study in Taiwan. (7th August 2017) - Yen, Yung-Feng; Lan, Yu-Ching; Huang, Chun-Teng; Jen, I-An; Chen, Marcelo; Lee, Chun-Yuan; Chuang, Pei-Hung; Lee, Yun; Morisky, Donalde E; Chen, Yi-Ming Arthur
Abstract : Human immunodeficiency virus (HIV) infection was an independent risk factor for incident autoimmune hemolytic anemia (AIHA). People living with HIV and receiving antiretroviral therapy were more likely to develop AIHA than those who not receiving the drugs. Abstract: Background: Currently, the association between human immunodeficiency virus (HIV) infection and subsequent development of autoimmune hemolytic anemia (AIHA) remains unclear. This nationwide population-based cohort study aimed to determine the association between incident AIHA and HIV infection in Taiwan. Methods: During 2000–2012, we identified people aged ≧15 years living with HIV (PLWH) from the Taiwan Centers for Disease Control HIV Surveillance System. Individuals were considered to be infected with HIV on the basis of positive results of an HIV type 1 Western blot. Age- and sex-matched controls without HIV infection were selected from the Taiwan National Health Insurance Research Database for comparison. All patients were followed until 31 December 2012 and observed for occurrence of AIHA. Results: Of 171468 subjects (19052 PLWH and 152416 controls), 30 (0.02%) had incident AIHA during a mean follow-up of 5.45 years, including 23 PLWH (0.12%) and 7 controls (0.01%). After adjustment for age, sex, and comorbidities, HIV infection was found to be an independent risk factor of incident AIHA (adjusted hazard ratio, 20.9; 95% confidence interval, 8.34–52.3). Moreover, PLWH who were receiving highly active antiretroviral therapy were more likely to develop AIHA than those who were not receiving these drugs (adjusted hazard ratio, 16.2; 95% confidence interval, 3.52–74.2). Conclusions: Our study suggests that HIV infection is an independent risk factor for incident AIHA.